Cytokeratin-18 and enhanced liver fibrosis scores in type 1 and type 2 diabetes and effects of two different insulins. (21st November 2017) - Sanyal, Arun; Cusi, Kenneth; Hartman, Mark L; Zhang, Shuyu; Bastyr, Edward J; Bue-Valleskey, Juliana M; Chang, Annette M; Haupt, Axel; Jacober, Scott J; Konrad, Robert J; Zhang, Qianyi; Hoogwerf, Byron J
Abstract : Data on cytokeratin-18 (K-18) and enhanced liver fibrosis (ELF) score in insulin-treated diabetes patients with non-alcoholic fatty liver disease (NAFLD) are limited. This study analyzed phase III data comparing basal insulin peglispro (BIL) and insulin glargine in type 1 (T1D), and type 2 diabetes (T2D) (insulin-naïve and insulin-treated). Alanine aminotransferase (ALT), K-18, ELF scores and liver fat content (LFC), measured by MRI, were obtained longitudinally. Baseline K-18 (U/L) was higher in T2D (range: 207‒247) than T1D (range: 148‒183), correlated with ALT in all populations (r (range) 0.264‒0.637, p<0.05), but with LFC only in T2D (r (range) 0.474‒0.586, p<0.05). K-18 increased significantly from baseline in BIL-treated, but not glargine-treated patients. Change from baseline (CFB) K-18 was significantly correlated with CFB in ALT in BIL-treated T2D populations. Baseline ELF scores were higher in T2D (range: 9.12‒9.20) than T1D (range: 8.24‒8.36), correlated with ALT in T1D only (0.209, p<0.05), and not correlated with LFC in any population. ELF scores increased significantly from baseline in BIL-treated but not glargine-treated patients. There were no correlations between CFB in LFC and ELF score at week 52 in any treatment group/population. In all BIL-treated populations, CFB in ALT and CFB in ELF score at week 52 were positively correlated. These data characterize associations of K-18 and ELF score with ALT and LFC in insulin-treated patients with T1D and T2D. Hepatopreferential insulins may be associated with increased K-18 and ELF scores but mechanisms and clinical significance are unknown. ClinicalTrials.gov identifiers are NCT01481779, NCT01435616, NCT01454284 and NCT01582451 .